OPTIMIZATION OF INTERACTIVE LEARNING MEDIA USAGE IN MADRASAH - Hosaini; Haya Haya; Abdul Halim (CV. ADIBA AISHA AMIRA, 2023)
Students should be motivated to actively participate in the learning process and be given many opportunities for initiative, creativity, and independence based on their interests and talents. The learning process should be dynamic, motivating, enjoyable, and challenging. An educational strategy known as interactive learning media blends technology with engaged student participation. It involves the use of various tools and platforms such as educational software, apps, learning videos, educational games, and online learning platforms. With this media, students at madrasas can actively participate in their learning, explore information, and collaborate with peers. The research was carried out using the literature study method. A literature review was used to collect data and information related to optimizing the use of interactive learning media in madrasas. This research discusses the definition, model, advantages and disadvantages, influence or impact of using interactive learning media in madrasas.